THE RECOVERY OF URBAN PRODUCTIVE LANDSCAPE: ISSUES AND PERSPECTIVES - Viola, Serena (European Scientific Journal, ESJ, 2015)
Over the centuries, architectural technologies have been a privileged means for a balanced interaction between natural and human creativity. The industrial development marked a turnaround for physical space, denying, by the name of economic growth, past synergies between spaces - technology - society. The persistence and pervasiveness of the economic and productive crisis are the reference scenario for the research commitment. The paper envisages a design approach mitigating the vulnerability of settlements, that lost their inner attitudes, through a recovery approach able to enhance past vocations. The ancient principle to use without consuming, supports a methodology based on the following actions: analyzing past transition drivers, outlining technological misalignments, building a transition agenda. The potential for growth is investigated, taking into account new requirements and previous performances. Focusing on manufacturing settlements located on the south of Italy, this research fits into the broader context of sustainability for places altered by technological transitions. The research assumes, as a privileged object of observation built environments hosting activities related to the agrifood processing, along the Vesuvius coast. Since ancient times, the need to create an added value, promotes interactions between products and places. A synergy, between technological culture and architecture, informs the quality of food, marking the urban environment in terms of constructive choices, distribution and morphology, environmental behaviour for spaces. The research carried out in the LRRM lab, tends to the identification of a systematic set of drivers of change that can support the recovery. The scientific commitment is based upon the awareness to recreate, within urban landscapes, the system of relations, human-scale, balanced to meet the physical, economic and social needs.